2016
DOI: 10.1080/1354750x.2016.1265007
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in release of cardiac troponin T after endurance exercise

Abstract: Post-exercise cardiac troponin release has been extensively described in athletic groups but little attention has been given to any role of sex in mediating this phenomenon. OBJECTIVE: We compared the release of cardiac troponin T (cTnT) after endurance running in training-experience, biological-age and maturity-matched young male and female runners. MATERIALS AND METHODS: Nineteen male (training history: 2.3±1.0 yr; mean age: 16.1±1.2 yr; Tanner stage: 3.7±0.6) and 19 female (training history: 2.2±1.0 yr; mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 30 publications
(39 reference statements)
4
24
0
1
Order By: Relevance
“…Using the hs-cTnT assay, higher baseline values in male than in female subjects have been previously reported in adults 30 and adolescents. 31 Others researchers have speculated a role for sex hormones to explain the sex differences in resting hs-cTnT concentration 15,31 where as we have speculated a role for sex differences in heart size. 5,6,32,33 This is an area that requires further research and insight to fully explain the mechanism(s) at play behind sex-based differences in the hs-cTnT response to exercise.…”
Section: The Impact Of Sex On Hs-ctnt and Nt-probnp Releasementioning
confidence: 63%
See 3 more Smart Citations
“…Using the hs-cTnT assay, higher baseline values in male than in female subjects have been previously reported in adults 30 and adolescents. 31 Others researchers have speculated a role for sex hormones to explain the sex differences in resting hs-cTnT concentration 15,31 where as we have speculated a role for sex differences in heart size. 5,6,32,33 This is an area that requires further research and insight to fully explain the mechanism(s) at play behind sex-based differences in the hs-cTnT response to exercise.…”
Section: The Impact Of Sex On Hs-ctnt and Nt-probnp Releasementioning
confidence: 63%
“…These results partially agree with those recently observed in male and female adolescent runners. 15 The authors reported that the response of cTnT after endurance exercise was substantially higher in male than female subjects, but at pre-exercise cTnT data were not different between 2 groups. In this study, exercise intensity was not controlled, and, therefore, we cannot rule out this factor as a contaminator variable.…”
Section: The Impact Of Sex On Hs-ctnt and Nt-probnp Releasementioning
confidence: 95%
See 2 more Smart Citations
“…This assay has a range from 3 to 10,000 ng l −1 , with a lower limit of detection of 3 ng l −1 . Serum cTnT concentrations that were below the limit of detection are reported as 1.5 ng l −1 (Kong et al., ; Tian et al., ). The coefficient of variation at a mean cTnT concentration of 13.5 ng l −1 is 5.2%.…”
Section: Methodsmentioning
confidence: 99%